Using ΦX174 DNA as an exogenous reference for measuring mitochondrial DNA copy number - Myers, Meagan B; Mittelstaedt, Roberta A; Heflich, Robert H (BioTechniques, 2009)
Quantitative real-time PCR has become a popular method to analyze and quantify changes in the copy number of mitochondrial DNA (mtDNA), and nuclear DNA (nDNA) is often used as an endogenous reference for mtDNA abundance. In our experience, using nDNA as a reference is problematic, due to differences in the extraction efficiency of nDNA and mtDNA and variation in the ploidy of experimental samples. Here, we report that the ratio of mtDNA to nDNA varies in repeated DNA extractions but that ΦX174 DNA, added before DNA extraction, is extracted with a similar efficiency to mtDNA, making it a suitable alternative reference for quantifying mtDNA copy number.